Explainable AI for Mental Health and Biomedical Decision Systems: A Comprehensive Review - Pramesti Dewi; Purwono Purwono; Annastasya Nabila Elsa Wulandari; Indah Trivilia (Peneliti Teknologi Teknik Indonesia, 2026)
The application of Artificial Intelligence (AI) in mental health is experiencing rapid development, while algorithmic transparency and clinical translation readiness still face fundamental obstacles. This review synthesizes empirical findings related to the use of Explainable Artificial Intelligence (XAI) in mental health and biomedical decision systems, focusing on three evaluative aspects, namely explainability architecture, validation strength, and clinical integration. The literature search followed the PRISMA 2020 guidelines across five major databases for publications from 2020 to 2026 and yielded nine studies that met the inclusion criteria. The synthesis results show the dominance of post-hoc approaches, particularly SHAP, which are commonly applied to ensemble and boosting models, while intrinsic models and counterfactual approaches are still rarely used. The majority of studies rely on internal validation, while independent external validation and prospective application in real clinical workflows are relatively limited. User-based evaluation of explainability has also been understudied, with algorithmic transparency more often understood as technical feature attribution rather than as a verified mechanism in clinical decision-making. These findings indicate a persistent gap between methodological advances and the level of clinical translation maturity. Explainability has not been systematically integrated with robust validation designs or user-oriented evaluations. This review proposes a translation evaluation framework that combines technical and clinical dimensions to assess the readiness for XAI implementation more comprehensively. The development of XAI in mental health requires evaluation standardization, strengthened external validation, and prospective testing focused on clinical impact and user trust.